A mass distribution letter as an early intervention for potential frequent callers. (2nd November 2022) - McDonnell, Aidan Joseph; McLaughlin, Russell; O'Neill, Ronan; Wolfe, Julia; Sinclair, Neil; Ruddell, Nigel
Abstract : Background: Intensive engagement with frequent callers (FCs) has been shown to be effective at reducing call volumes and producing positive outcomes for service users. Aims: This study aimed to examine the impact of sending a mass distribution letter to potential frequent callers (PFCs) on emergency call volumes. Methods: A standardised letter containing advice and information for newly identified PFCs was introduced in an attempt to signpost service users to more appropriate care providers before they met the FC criteria. In total, 96 letters were distributed to PFCs and their impact on emergency call volumes was assessed. Findings: Emergency calls decreased from 439 to 187 in the 10 weeks following letter distribution, equating to an average reduction of 57.5%. Conclusion: An association was found between letter distribution and a reduction in emergency calls. Future opportunities for development include an emphasis on feedback from recipients and determination of specific causality.